Co3S4 nanosheets on Ni foam via electrodeposition with sulfurization as highly active electrocatalysts for anion exchange membrane electrolyzer. (1st January 2020) - Park, Yoo Sei; Lee, Jeong Hun; Jang, Myeong Je; Jeong, Jaehoon; Park, Sung Min; Choi, Woo-Sung; Kim, Yangdo; Yang, Juchan; Choi, Sung Mook
Abstract: Co3 S4 nanosheets on Ni foam (NS/NF) were prepared by sulfurization for various time after calcination of electrodeposited Co(OH)2 . In our FE-SEM images, we observed that Co3 S4 NS was vertically, or obliquely, deposited on the Ni foam. As a result, the structure contained more active sites, and active sites were highly accessible to the electrolyte for the hydrogen evolution reaction (HER). Furthermore, results of XPS and XRD analysis confirmed S-conversion from Co3 O4 to Co3 S4 during sulfurization. 3-Co3 S4 NS/NF with sulfurization for 3 h exhibited the highest sulfur content, while Co3 S4 began to desulfurize to Co9 S8 after sulfurization for 4 h. The 3-Co3 S4 NS/NF electrocatalyst showed a lowest overpotential of 93 mV at −10 mA/cm 2, with a Tafel slope of −55.1 mV/dec in N2 -purged 1 M KOH. Also, the single cell anion exchange membrane water electrolyzer (AEMWE) showed a high current density of 431 mA/cm 2 with cell voltage 2.0 Vcell at 40–45 °C. Graphical abstract: Image 1 Highlights: The Co3 S4 nanosheets on Ni foam was prepared by electrodeposition and sulfurization for various time. The Co3 S4 nanosheets on Ni foam with sulfurization for 3 h indicated the highest sulfur content. The Co3 S4 nanosheets on Ni foam with sulfurization for 3 h showed a lowest overpotential of 93 mV at −10 mA/cm 2 in 1 M KOH. The single cell anion exchange membrane water electrolyzer (AEMWE) showed a high current density of 431 mA/cm 2 at 2.0 Vcell .